The Effect of Independent Commissioners, Foreign Ownership, and Asset Efficiency on Tax Avoidance (Study on Energy Sector Companies in the Oil, Gas, and Coal Subsector Listed on the IDX for the 2019–2023 Period) - Fikri Imam Baehaki; Surifah Surifah (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effect of independent commissioners, foreign ownership, and asset efficiency on tax avoidance in energy sector companies specifically those in the oil, gas, and coal subsectors isted on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. Using purposive sampling, a total of 220 observations were obtained. The research employs a quantitative approach with panel data regression analysis, and the Random Effect Model (REM) was selected using EViews 12 software. The results show that both independent commissioners and foreign ownership have a significant negative effect on tax avoidance, while asset efficiency has no significant effect. These findings indicate that the presence of independent commissioners and foreign investors plays a crucial role in reducing tax avoidance practices, whereas asset efficiency does not appear to influence tax-related decisions. This supports agency theory, which suggests that oversight from independent parties and involvement of foreign shareholders can reduce information asymmetry and managerial opportunism. The theoretical contribution of this study lies in reinforcing the importance of corporate governance mechanisms in limiting tax avoidance strategies that could be detrimental to the state.